RNA interference analysis of potential functions of cyclin A in the reproductive development of male oriental river prawns (Macrobrachium nipponense) - Zhang, Wenyi; Xiong, Yiwei; Wang, Pengchao; Chen, Tianyong; Jiang, Sufei; Qiao, Hui; Gong, Yongsheng; Wu, Yan; Jin, Shubo; Fu, Hongtuo (Frontiers in Genetics, 2022)
Cyclin A (CycA) plays essential roles in regulating multiple steps of the cell cycle, and it affects gonad development in mammals and invertebrates. Previous RNA interference (RNAi) analysis revealed that knocking-down the expression of CycA in female oriental river prawns (Macrobrachium nipponense) inhibited ovarian development. CycA was also predicted to have regulatory roles in reproductive development of male M. nipponense based on significant changes of Mn-CycA expression after eyestalk ablation. The goal of this study was to investigate the potential functions of CycA in the reproductive development of male M. nipponense using RNAi and histological observations. Quantitative real-time PCR analysis revealed that both single-side and double-side eyestalk ablation stimulated the expressions of Mn-CycA, and the expression was higher in prawns with double-side eyestalk ablation (p < 0.05). Mn-CycA expression was significantly higher in the testis and androgenic gland during the reproductive season than during the non-reproductive season (p < 0.05). In the RNAi analysis, Mn-CycA expression significantly decreased after prawns were injected with dsCycA, and the expression of insulin-like androgenic gland hormone (Mn-IAG) also decreased as Mn-CycA expression decreased. This result indicated that CycA positively regulated the expression of IAG in M. nipponense. Histological observations revealed that the number of sperm decreased dramatically to <5% of the total cells in the testis of the dsCycA-treated group compared to that of control group on day 14, indicating that knockdown of Mn-CycA expression inhibited testis development by affecting the expression of Mn-IAG in M. nipponense. These results highlighted the functions of CycA in male reproductive development of M. nipponense, which can be applied to future studies of male reproduction in other crustacean species.